Resistensi Masyarakat Rempang Atas Pelaksanaan Proyek Strategis Nasional (PSN) Rempang Eco City Dalam Wilayah Batam, Provinsi Kepulauan Riau - Rizkiani, Fadhilah; Syafril, Syafril; Nopriyasman, Nopriyasman (Jurnal Ilmiah Global Education, 2025)
The Rempang community's resistance to the Rempang Eco City National Strategic Project (PSN) is not just a simple rejection, but rather a resistance to fight for and defend the basic rights, cultural identity, and legality of the village they have occupied for generations from generation to generation which certainly has the history and culture of the village. Development for the progress that brings prosperity to the community should be built on a foundation of justice and community participation, especially those directly affected by the development, not the sacrifice and eviction of villages that have been occupied for a long time and have a cultural identity and history within them. The Rempang community supports development if the development does not harm the community, for example, development that can advance Rempang Island by utilizing and advancing the natural environment that makes Rempang Island more famous for its local wisdom.